Subtraction neglect in perceptions of climate action strategies - Suter, Manuel; Nielsen, Kristian Steensen; Berger, Sebastian (Journal of Environmental Psychology, 2025)
Research suggests that individuals often overlook beneficial subtractive strategies when solving problems. Subtractive strategies, which include reducing demand for goods and services (e.g., reducing car use), have a high climate mitigation potential. Yet, these may be systematically overlooked in favor of additive strategies like adopting new technologies (e.g., buying an electric car). This Registered Report investigates subtraction neglect in the context of personal climate action. When asked to think of the most effective personal climate mitigation actions, does priming people to think about additive and subtractive strategies increase the likelihood that they suggest subtractive climate actions? We investigate this research question via an online experiment conducted in the United Kingdom. Participants who received a brief prompt introducing both strategy types proposed significantly more subtractive actions than those who were not made aware of additive and subtractive strategies. The findings suggest that raising awareness of subtractive strategies can shift attention toward underused yet impactful climate actions.
Keywords: Cognitive bias; Online experiment; Personal climate mitigation; Pro-environmental behavior; Subtraction neglect; Sufficiency